Ecologia e morfoanatomia de plântulas ocorrentes na planície de inundação do alto rio Paraná. - Pisicchio, Cristina Moreira (2011)
It was determined which components edaphic or topographic could explain the distribution of seedlings Psychotria carthagenensis, Psychotria capillacea, Triplaris american, Celtis iguaneae, Cecropia pachystachya and Piper tuberculatum, and describe the morphology and anatomy seedlings of P. carthagenenensis and P. capillacea. For this, sampled was 600 m2, the remaining forest located on the island Puerto Rico, in three transects of 100m, in plots of 2 x 2 m in March 2008, July 2008 and February 2009. Soil samples were collected at 10 points per transect between July 2008 and were carried out chemical analysis, particle size and moisture content. The topography was prepared in the same transects through hose graduated. For the description morphoanatomical seedlings of P. carthagenensis and P. capillacea, 10 individuals of each species were collected in the study area, together with the substrate, and were described the morphology and anatomy of root, hypocotyl, cotyledons, eophylls, colleters and stipules. Were fixed in 50% FAA, embedded in hydroxy ethyl methacrylate, sectioned in a rotation microtome and stained with toluidine blue 0.05%. The material was also analyzed by SEM. The soil is classified as Tb Fluvic Dystrophic typical. The two species of Psychotria, Celtis and Cecropia were associated with potassium, calcium, pH, fine particulate organic matter, phosphorus and Piper and Triplaris with aluminum and soil moisture. The Canonical Correspondence Analysis revealed gradient of increasing acidity, moisture and higher levels of calcium, magnesium and aluminum with the distance of river. Seedlings of both species of Psychotria are fanerocotylar epigeal. The primary root and hypocotyl is diarchic transition structure has root-stem. The cotyledons are foliaceous and dorsiventral. The epicotyl stem structure has eustele. Eophylls opposites are prescribed, petiolate, hipostomatic and dorsiventral. Stipules present interpetiolar colleters of tipo 'S-standard'. The two species are morphologically and anatomically similar, differing only in the shape of cotyledons and trichomes eophylls.